Design conversacional de chatbots: cultura, linguagem e participação - Monteiro, Mateus de Souza; Pereira, Vinícius Carvalho; Salgado, Luciana Cardoso de Castro (Anais Estendidos do Simpósio Brasileiro de Sistemas Colaborativos (SBSC), 2023)
The challenges in conversational design of chatbots that consider domain and/or user cultural issues are diverse. Among them, the lack of conceptual and/or theoretical approaches to guide the designer during the conversational design process. As a result, designers often rely on their own assumptions and linguistic preferences in conversation design. In this work, we discuss how the areas of HCI and CSCW can contribute to the inclusion of cultural issues in the participatory design process of conversational agents.